2009
DOI: 10.1016/s1701-2163(16)34155-x
|View full text |Cite
|
Sign up to set email alerts
|

Management Guidelines for Obstetric Patients and Neonates Born to Mothers With Suspected or Probable Severe Acute Respiratory Syndrome (SARS)

Abstract: The Society of Obstetricians and Gynaecologists of Canada. Recommendations 1. All hospitals should have infection control systems in place to ensure that alerts regarding changes in exposure risk factors for SARS or other potentially serious communicable diseases are conveyed promptly to clinical units, including the labour and delivery unit. (III-C) 2. At times of SARS outbreaks, all pregnant patients being assessed or admitted to the hospital should be screened for symptoms of and risk factors for SARS. (III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 34 publications
0
26
0
3
Order By: Relevance
“…The literature search identified 987 articles. After title and abstract screening, 16 papers were selected for full‐text review; among those, there was one retrospective cohort study [14]; four case series [15‐18]; four case reports [19‐22]; and seven expert opinion articles [1, 12, 23‐27] (Table 1). Backward citation identified additional reports; however, the information relevant to regional anaesthesia was already presented in original papers in the initial search.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 987 articles. After title and abstract screening, 16 papers were selected for full‐text review; among those, there was one retrospective cohort study [14]; four case series [15‐18]; four case reports [19‐22]; and seven expert opinion articles [1, 12, 23‐27] (Table 1). Backward citation identified additional reports; however, the information relevant to regional anaesthesia was already presented in original papers in the initial search.…”
Section: Resultsmentioning
confidence: 99%
“…We followed our institution protocol for patients with MERS and referred to the SARS obstetrics guidelines. According to the management guidelines for obstetric patients with SARS [ 12 ], all deliveries should be managed in a designated negative-pressure isolation room and by designated personnel with specialized infection control PPE.…”
Section: Discussionmentioning
confidence: 99%
“…With the currently limited knowledge about MERS-CoV epidemiology and pathophysiology, it is prudent to review observed associations between pregnancy outcomes and other severe respiratory pathogens. Complications such as maternal mortality and stillbirth have been reported among pregnant women with severe respiratory infections caused by SARS coronavirus (SARS-CoV) [ 4 ], influenza A virus subtype H1N1 [ 5 , 6 ], and other viruses causing pneumonia [ 7 ]. Uncomplicated pregnancies lead to physiologic changes resulting in altered pulmonary and immunologic function [ 8 , 9 ], including a 20% increase in maternal oxygen consumption, a 10%–25% decrease in functional residual capacity, and significantly increased forced vital capacity after 14–16 weeks gestation.…”
Section: Discussionmentioning
confidence: 99%